2017
DOI: 10.1080/10641963.2017.1324480
|View full text |Cite
|
Sign up to set email alerts
|

mRNA levels of circadian clock components Bmal1 and Per2 alter independently from dosing time-dependent efficacy of combination treatment with valsartan and amlodipine in spontaneously hypertensive rats

Abstract: Chronopharmacological effects of antihypertensives play a role in the outcome of hypertension therapy. However, studies produce contradictory findings when combination of valsartan plus amlodipine (VA) is applied. Here, we hypothesized different efficacy of morning versus evening dosing of VA in spontaneously hypertensive rats (SHR) and the involvement of circadian clock genes Bmal1 and Per2. We tested the therapy outcome in short-term and also long-term settings. SHRs aged between 8 and 10 weeks were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…With the study length being the only difference between these two studies, this fact might indicate that the duration of treatment can also influence the chrono-effect. Similar results were also confirmed in preclinical settings (Potucek et al, 2017).…”
Section: Fixed Combination Therapysupporting
confidence: 76%
“…With the study length being the only difference between these two studies, this fact might indicate that the duration of treatment can also influence the chrono-effect. Similar results were also confirmed in preclinical settings (Potucek et al, 2017).…”
Section: Fixed Combination Therapysupporting
confidence: 76%
“…Potucek, et al evaluated the efficacy of morning versus evening dosing of 10 mg/kg of valsartan and 4 mg/kg of amlodipine in spontaneously hypertensive rats, and observed that only morning dosing resulted in significant BP control after short-term (1 week) treatment while both dosing groups gained similar superior results in BP control after long-term (6 weeks) treatment. This study indicated that morning administration proved to be advantageous due to earlier onset of antihypertensive action whereas the efficacy of longterm treatment was regardless of administration time [52].…”
Section: Rivaroxabanmentioning
confidence: 78%
“…In this study, single nucleotide polymorphism (SNP) databases were analyzed to discover that SNPs in the Bmal1 gene are associated with hypertension in humans [28]. In a recent study, SHR treated with a combination of a calcium channel blocker and an angiotensin receptor blocker to reduce blood pressure also exhibited a reduction in Bmal1 mRNA levels in the kidneys [29]. Inducible, kidney-specific knockout mice have been studied to determine the role of Bmal1 specifically in renal nephrons using Bmal1 lox/lox/Pax8-rtTA/LC1 mice [30].…”
Section: Sodium Handlingmentioning
confidence: 99%
“…The Hygia Project is an ongoing assessment of a much larger population where clinical reports are analyzed from multiple health facilities [59,60]. Additionally, a recent study in rats used hypertensive therapy in the morning and evening and found that treatment before the inactive period was more beneficial for the rats than before the active [29]. However, this was only seen with short-term treatment of 1 week and no difference was seen with long-term treatment [29].…”
Section: Implications Of the Kidney Clock For Human Healthmentioning
confidence: 99%
See 1 more Smart Citation